Peti Diklat: Sebuah Model Flipped Classroom dengan Pendekatan Cognitive Apprenticeship untuk Pelatihan Guru Baru - Susi Susanti; Khaerudin Khaerudin; Etin Solihatin (Jurnal Paedagogy, 2022)
This research aims to improve the Kaeophanuek & Chookerd flipped classroom design by accommodating activities in the form of practice and simulation of knowledge gained in real life to be more suitable to apply in the workplace. This study used Research and Development (R&D). Preliminary research was conducted at the Integrated Islamic School involving 15 new teachers from Kindergarten, Elementary School, Junior High School, Senior High School, and Vocational Schools. The results of this study will develop a Flipped Classroom with a Cognitive Apprenticeship approach for training new teachers named PETI DIKLAT. To realize this model, research was conducted using the Integrated Learning Design Framework (ILDF) development model combined with the cart learning design model.